Does Bright Light Counteract the Post-lunch Dip in Subjective States and Cognitive Performance Among Undergraduate Students? - Zhou, Ying; Chen, Qingwei; Luo, Xue; Li, Le; Ru, Taotao; Zhou, Guofu (Frontiers in Public Health, 2021)
The post-lunch dip in alertness and performance was widely experienced during the early afternoon. Taking a short nap was documented as a practical strategy for habitual nappers to counteract the decline of alertness and performance. Yet, it remains unknown whether bright light exposure in the early afternoon working hours could alleviate the performance deficits caused by a post-lunch nap loss for habitual nappers. Seventeen undergraduate students who had long-term habit of taking a post-lunch nap were assigned to three interventions: (1) a short nap + normal indoor light (100 lx, 4000 K at eye level); (2) no nap + normal indoor light and (3) no nap + blue-enriched bright light (1000 lx, 6500 K at eye level), in which subjective alertness (Karolinska Sleepiness Scale), mood (Positive and Negative Affect Schedule) and task performance in sustained attention (Psychomotor Vigilance Test, PVT), response inhibition (Go/No-go task) and working memory (Paced visual serial addition task, PVSAT) were measured. Results showed that an midday nap deprivation impaired subjective states and cognitive function, while bright light vs. normal indoor light exposure in the early afternoon significantly reduced the negative mood and subjective sleepiness, increased reaction speed in Go/No-go task and accuracy and speed in PVSAT task, while subjective positive mood and performance in PVT task remained unaffected with bright light intervention. These findings suggested that bright light exposure could be a potential strategy for those who were suffering from drowsiness and low efficiency following a habitual midday nap loss.